Posttraumatic Headache - Heinzelmann, Morgan; Woods, Christine; Vargas, Bert B.; Stokes, Mathew (Seminars in Neurology, 2022)
Posttraumatic headache (PTH) is the most common secondary headache disorder, accounting for approximately 4% of all headache disorders. It is the most common symptom following concussion (mild traumatic brain injury) and can be debilitating for many who have persistent symptoms. With a recent increase in public awareness regarding traumatic brain injury, there has been a corresponding increase in PTH research. The pathophysiology of PTH remains poorly understood and the underlying mechanisms are likely multifactorial. Diagnosis of PTH is dependent on a temporal relationship to a head injury. PTH often resembles common primary headache phenotypes. Treatment of PTH utilizes known treatments for these other headache phenotypes, as there is no currently approved treatment specifically for PTH. Moving forward, further studies are needed to better define and validate the definition of PTH, understand the underlying pathophysiology, and find more specific treatments.
Keywords: posttraumatic headache; traumatic brain injury; concussion; headache